Current trends in scientific computing: ICM 2002 Beijing Satellite Conference on Scientific Computing, August 15-18, 2002, Xi'an Jiaotang University, Xi'an, China - Chen, Zhangxin (Contemporary mathematics, 2003)
This volume contains 36 research papers written by prominent researchers. The papers are based on a large satellite conference on scientific computing held at the International Congress of Mathematicians (ICM) in Xi'an, China. Topics covered include a variety of subjects in modern scientific computing and its applications, such as numerical discretization methods, linear solvers, parallel computing, high performance computing, and applications to solid and fluid mechanics, energy, environment, and semiconductors. The book will serve as an excellent reference work for graduate students and researchers working with scientific computing for problems in science and engineering.